2020
DOI: 10.1038/s41438-020-0339-8
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated mutagenesis of VvMLO3 results in enhanced resistance to powdery mildew in grapevine (Vitis vinifera)

Abstract: Grapevine (Vitis vinifera), one of the most economically important fruit crops in the world, suffers significant yield losses from powdery mildew, a major fungal disease caused by Erysiphe necator. In addition to suppressing host immunity, phytopathogens modulate host proteins termed susceptibility (S) factors to promote their proliferation in plants. In this study, CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated 9) technology was used to enable the targeted mutagenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(71 citation statements)
references
References 51 publications
0
69
0
2
Order By: Relevance
“…‘Seishi’ × M. pumila ) 23 25 , orange ( Citrus sinensis (L.) Osbeck) 26 , 27 , kiwifruit ( Actinidia deliciosa ) 28 , 29 , and grapevine ( Vitis vinifera ) 12 , 30 33 . However, the extent of off-target mutations in CRISPR/Cas9-edited fruit trees is still not completely examined and has mainly been investigated using target sequencing 12 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…‘Seishi’ × M. pumila ) 23 25 , orange ( Citrus sinensis (L.) Osbeck) 26 , 27 , kiwifruit ( Actinidia deliciosa ) 28 , 29 , and grapevine ( Vitis vinifera ) 12 , 30 33 . However, the extent of off-target mutations in CRISPR/Cas9-edited fruit trees is still not completely examined and has mainly been investigated using target sequencing 12 , 31 , 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past eight years, there have been many reports of creating genome-edited plants with resistance to viral, bacterial, and fungal diseases in different plant species using CRISPR/Cas technology ( Zhang et al, 2021 ). These include CRISPR/Cas9 knock-outs of the following genes: mlo for plant resistance to powdery mildew in wheat ( Wang et al, 2014 ), tomato ( Nekrasov et al, 2017 ; Martínez et al, 2020 ) and grapevine ( Wan et al, 2020 ), pmr4 for plant resistance to powdery mildew in tomato (Santillán Martínez et al, 2020), 14-3-3 gene for resistance to Verticillium dahlia in cotton ( Zhang ZN et al, 2018 ), crt1a for resistance to Verticillium longisporum in both Arabidopsis thaliana and oilseed rape ( Pröbsting et al, 2020 ), OsERF922 for resistance to Magnaporthe oryzae in rice ( Wang et al, 2016 ), Clpsk1 for resistance to Fusarium oxysporum f. sp. niveum in watermelon ( Zhang et al, 2020 ), eif4e for resistance to Cucumber vein yellowing virus , Zucchini yellow mosaic virus , and Papaya ring spot mosaic virus‐W in cucumber ( Chandrasekaran et al, 2016 ), CsWRKY22 for resistance to Xanthomonas citri subsp.…”
Section: Crispr/cas Is a Robust And Powerful Tool For Precision Brementioning
confidence: 99%
“…Recently, a genome-wide survey of suitable sites for CRISPR/Cas9 genome editing has been conducted in grapevine ( Wang et al, 2016 ) and successful attempts to actually generate genome-edited grapevine have been reported ( Ren et al, 2016 ; Wang et al, 2016 ). Although the latter were just merely proof of concept attempts, Wan et al (2020) reported this technology to generate grapevine plants with enhanced powdery mildew resistance through Mlo gene edition. The authors reported a 38.5% successful gene edition rate, a value lower to those previously reported in rice (84.3% on average) but comparable to those obtained in Arabidopsis (35.6% on average) ( Ma et al, 2015 ).…”
Section: Controlling the Genome And Its Expressionmentioning
confidence: 99%